2018
DOI: 10.3348/kjr.2018.19.6.1099
|View full text |Cite
|
Sign up to set email alerts
|

No-Touch Radiofrequency Ablation of VX2 Hepatic Tumors In Vivo in Rabbits: A Proof of Concept Study

Abstract: ObjectiveIn a proof of concept study, we compared no-touch radiofrequency ablation (NtRFA) in bipolar mode with conventional direct tumor puncture (DTP) in terms of local tumor control (LTC), peritoneal seeding, and tumorigenic factors, in the rabbit VX2 subcapsular hepatic tumor model.Materials and MethodsSixty-two rabbits with VX2 subcapsular hepatic tumors were divided into three groups according to the procedure: DTP-RFA (n = 25); NtRFA (n = 25); and control (n = 12). Each of the three groups was subdivide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…NT-RFA : bipolar RFA was performed using TICW electrodes and the same generator unit used in the conventional RFA group. For the NT-RFA technique, the two tines of TICW electrodes were inserted into the perimeter of the index tumor (generally 3–5 mm from the margin of the target tumor) at an inter-electrode distance of 2–3 cm, depending on tumor size, under the guidance of real-time US-CT/MR fusion imaging [ 14 15 17 21 ]. An example case is shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…NT-RFA : bipolar RFA was performed using TICW electrodes and the same generator unit used in the conventional RFA group. For the NT-RFA technique, the two tines of TICW electrodes were inserted into the perimeter of the index tumor (generally 3–5 mm from the margin of the target tumor) at an inter-electrode distance of 2–3 cm, depending on tumor size, under the guidance of real-time US-CT/MR fusion imaging [ 14 15 17 21 ]. An example case is shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The rate of successful no-touch RFA, defined as performing RFA without violation of the tumor during the procedure, was also recorded. In addition, technical success of RFA was de-no-touch RFA provided good local tumor control and a lower rate of recurrence (11,12). Several clinical studies have also reported that no-touch RFA may provide an LTP rate as low as 6% at 5 years and that it also has the potential to prevent intrasubsegmental recurrence (10,13).…”
Section: Rfa Procedures and Follow-upmentioning
confidence: 99%
“…The first advantage is the ablative volume could be selectively The second advantage is that ATA greatly reduces the heat sink effect and, in turn, increases local heat accumulation and ensure irreversible cell damage in the tumor. Previous reports 15,27,28 stated that the heat sink effect caused by intratumoral or peritumoral blood vessels was correlated with the incidence of LTP. Some researchers [18][19][20] have proposed that ablation of the feeding artery may prevent LTP and intrahepatic tumor recurrence by decreasing the heat sink effect.…”
Section: Discussionmentioning
confidence: 95%